Awareness of Asbestos and Action Plans for Its Exposure can Help Lives Exposed to Asbestos - Hu-Jang Lee; Eun-Kee Park; Donald Wilson; Engin Tutkun; Chulho Oak (Elsevier, 2013)
Despite the fact that asbestos is a known carcinogen to humans, it is still used in industrialized countries, especially Asian countries. The global incidence of asbestos-related diseases (ARDs) due to the past use of asbestos, continues to increase, although many countries have adopted a total ban on asbestos use. The implementation of effective strategies to eliminate ARDs is therefore an important challenge in Asia, where asbestos is still mined and consumed. Collaborative efforts and strategies at the local and international levels are vital, in the pursuit toward the elimination of ARDs in this region.